2021
DOI: 10.1016/j.hroo.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset atrioventricular block after transcatheter aortic valve replacement

Abstract: Background Conduction disturbances leading to permanent pacemaker implantation (PPI) rarely occur late after transcatheter aortic valve replacement (TAVR). The clinical features of this phenomenon and its association with periprocedural conduction disturbances remain uncertain. Objectives We aimed to determine the incidence and characteristics of late-onset atrioventricular block (AVB) after TAVR. Methods This single-center study included 246… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Evidence from previous studies showed that PPMI can occur beyond 30 days after TAVR [ 33 ]. The medical records of patients with PPMI beyond 30 days after TAVR in the derivation set showed that most of these patients experienced amaurosis or syncope within 30 days after TAVR, but did not seek appropriate medical treatment in time.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies showed that PPMI can occur beyond 30 days after TAVR [ 33 ]. The medical records of patients with PPMI beyond 30 days after TAVR in the derivation set showed that most of these patients experienced amaurosis or syncope within 30 days after TAVR, but did not seek appropriate medical treatment in time.…”
Section: Discussionmentioning
confidence: 99%
“…Those with transient atrioventricular block are at risk for recurrence of atrioventricular block, usually within days, although atrioventricular block even later than 30 days can occur. 1 Therefore, late atrioventricular block was not anticipated in this patient before symptoms. Approximately 15% of patients receive a permanent pacemaker after TAVR.…”
mentioning
confidence: 85%
“…Several studies showed that chronic right ventricular pacing has been associated with adverse effects on ventricular function and an increased risk of morbidity and mortality in long‐term follow‐up of non‐TAVR patients 4–6 . However, long‐term data on the prognostic impact of post‐TAVR PPI remain controversial 7–9 . We now report the impact of new PPI on clinical outcomes in patients undergoing TAVR at our center.…”
Section: Introductionmentioning
confidence: 93%
“…[4][5][6] However, long-term data on the prognostic impact of post-TAVR PPI remain controversial. [7][8][9] We now report the impact of new PPI on clinical outcomes in patients undergoing TAVR at our center.…”
Section: Introductionmentioning
confidence: 99%